Penggunaan Data Mining Saat Ini Dan Tantangannya Di Masa Depan (Jurnal Matematika, Statistika dan Komputasi, 2018)
This paper begins by describing the main activities involved in the data mining process and highlight the two major styles of data mining: supervised and unsupervised. It then describes two “hot” areas where data mining applications are being used successfully business database systems and the Internet. Finally, it concludes by examining the challenges and research issue data mining will face in the future